Empowering fathers through social work : barriers and solutions to father engagement in parenting programmes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Manawatū, New Zealand - Gray, Melissa Joy (Massey University, 2021)
This thesis explored six social workers’ perspectives on potential barriers and solutions to father engagement when delivering a parenting programme. Engagement with fathers in parenting programmes is an under-researched area and this thesis adds to this body of knowledge. This qualitative research was conducted using an interpretivist approach drawing on social constructivism as a theoretical framework. Semi-structured interviews with six social workers allowed for flexibility and the collection of meaningful data. Thematic analysis was used to find meaning in the data, where there was a consensus among social workers. The findings of this thesis indicate that social constructions of parental roles impact on father engagement in parenting programmes. Perceptions from social workers, other professionals, communities and on a societal level may be marginalising fathers from attending or feeling included in parenting programmes. Gender safety for fathers in a female dominated social work industry was also thought to impact on engagement. Numerous practical factors also effect the level of father engagement in parenting programmes. It is recommended that social workers strive for father empowerment on different levels to ensure that fathers are valued and can engage in parenting programmes.
Keywords: 440901 Clinical social work practice